Power and Resistance in ‘Tamasoma Jyotirgamaya’: A CDA Approach to Television Talk Shows in Nepal - Gyawali, Ramesh (A Bi-annual South Asian Journal of Research & Innovation, 2024)
Television interview programs entail the circulating power on the part of the interviewer based on the background of media power; simultaneously, the interviewee attempts to maintain resistance as the counter power circulation emerges out of the socio-political underpinnings. This study aims at denaturalizing the strategy of circulating power and resistance and exploring the unequal relationship between the participants of discourse, especially of the popular television interview program ‘Tamasoma Jyotirgamaya’ aired on AP1 HD television. The demystifying process was established through the analysis of the language of the spoken texts unfolding the strategy of representation, concealment, and construction of identity of self and others, mainly through the play of ideology and hegemony in relation to power through the data collected from official YouTube channel of AP1 HD and Approached with CDA to reveal the underlying intentions of power and resistance. The research reveals that the interviewer, as an established journalist, exercises power over the interviewee; however, the interviewee, as a political person, makes efforts to resist. Talk show program, as a form of media discourse, cultivates the ideological functions for both power and resistance.